Stage-dependent dynamics and modulation of spontaneous waves in the developing rabbit retina - Syed, Mohsin Md (Blackwell Science Inc, 2004)
We report here a systematic investigation of the dynamics, regulation and distribution of spontaneous waves in the rabbit retina during the course of wave development prior to eye opening. Three major findings were obtained in this longitudinal study. (1) Spontaneous retinal waves underwent three developmental stages, each of which displayed distinct wave dynamics, pharmacology and mechanism of generation and regulation. Stage I waves emerged prior to synaptogenesis and appeared as frequent, fast propagating waves that did not form spatial boundaries between waves. These waves could be inhibited by blockers of gap junctions and adenosine receptors, but not by nicotinic antagonists. Stage I waves lasted about one day (around embryonic day 22) and then switched rapidly to stage II, resulting in slower and less frequent waves that could be blocked by nicotinic antagonists and had a characteristic postwave refractory period and spatial boundaries between adjacent waves. Immediately after the transition from stage I to stage II, the waves could be reverted back to stage I by blocking nicotinic receptors, indicating the presence of mutually compensatory mechanisms for wave generation. Stage III waves emerged around postnatal day 3–4 (P3–4), and they were mediated by glutamtergic and muscarinic interactions. With age, these waves became weaker, more localized and less frequent. Spontaneous waves were rarely detected after P7. (2) GABA strongly modulated the wave dynamics in a stage- and receptor type-dependent manner. At stage I, endogenous GABA(B) activation downregulated the waves. The GABA(B) modulation disappeared during stage II and was replaced by a strong GABA(A/C)-mediated inhibition at stage III. Blocking GABA(A/C) receptors not only dramatically enhanced spontaneous stage III waves, but also induced propagating waves in >P7 retinas that did not show spontaneous waves, indicating a role of GABA inhibition in the disappearance of spontaneous waves. (3) Spontaneous retinal waves were found in both the inner and outer retina at all three stages. The waves in the outer retina (ventricular zone) also showed stage-dependent pharmacology and dynamics. Together, the results revealed a multistaged developmental sequence and stage-dependent dynamics, pharmacology and regulation of spontaneous retinal waves in the mammalian retina. The presence of retinal waves during multiple developmental stages and in multiple retinal layers suggests that the waves are a general developmental phenomenon with diverse functions.